Strategic Marketing Plan for APPLE Inc. - Muhammad Anas KHALID; Viktoria VIDA (Network Intelligence Studies, 2023)

(untitled)
This study aims to explore the inner workings of Apple Inc. to gain a deeper understanding of the company's success and to identify opportunities for further growth and improvement. Through an analysis of market trends, consumer behaviour, and Apple Inc.'s current marketing strategies, this research will develop a comprehensive marketing plan that addresses key areas of growth and improvement. Furthermore, the effectiveness of this research will be evaluated using various marketing research tools (SWOT matrix, TOWS matrix, IFE matrix, EFE matrix, IE matrix, PESTEL analysis, Porter Five Forces Model and CPM matrix). This study will provide new information and strategies for new organizations trying to enter the industry and want to be successful. It will also contribute to the existing body of knowledge in the field of marketing, specifically as it pertains to companies operating in the technology industry. Additionally, the research will also serve as a useful reference for businesses and organizations in similar industries, as well as for marketing professionals looking to gain a deeper understanding of the dynamics of the technology industry. It will also benefit academicians and researchers studying the field of marketing and technology.